Associate Professor Ts. Dr. Muhammad Aizzat produces advanced robotics that benefits in TVET - Nur Hartini, Mohd Hatta (UMPSA, 2024)
PEKAN, 21 May 2024 – The field of advanced robotics is increasing in the world market, but Malaysia is still lacking expertise.